Design of Smart College Using Raspberry Pi (University of Khartoum Engineering Journal, 2022)
Smart College refers to the technologies that have been developed to satisfy the needs of students and teachers in order to feel more confident in the education environment. These technologies facilitate the process of entry and exit and help to organize the time, these technologies also save the use of energy. The proposed design in this paper offers a complete control of all the electronic devices in the hall, whether within the collage or remotely from any place outside the college by using either android system or Wi-Fi technology. The design guarantees the system security, it does not allow anyone who is not authorized to enter or access it. The basic architecture of this design consists of raspberry pi device, group of drivers and relays .The system enables the manager of it to adjust the operation time of gates which controls the opening and closing time of the doors at specific time selected by the manager. This paper also includes a survey of most of the existed works related to this field. The proposed system has been experimentally proven to work successfully and it has high level of reiliabity and authentication.